CALCULATING SPACE VELOCITIES (U,V,AND W) FOR STARS INTHE HALO OF OUR GALAXY - Abed Lateef, Abbas (Iraqi Journal of Science, 2024)
Space velocities (U,V,and W)for many stars in the halo of our galaxy werecalculated by choosing A,G and K spectral type stars at a distance nearly 10 pc. Itwas found that some of these stars represent a Local Association group (kinematicstream), the stars of this group are sharing in similar 3-D kinematic motion in thegalaxy, in the solar neighborhood. The results displayed that these velocities are in agood correlation with each other .